Remdesivir and its antiviral activity against COVID-19: A systematic review - Andri Frediansyah; Firzan Nainu; Kuldeep Dhama; Mudatsir Mudatsir; Harapan Harapan (Elsevier, 2021)
Background: The aim of this study was to summarize the antiviral activities of remdesivir against SARS-CoV-2, the causative agent of COVID-19. Methods: Available publications were systematically explored on some databases and gray literature was examined. Publications were discussed narratively. Results: Remdesivir inhibits SARS-CoV-2 replication, reduces viral load, and exerts protective effects in SARS-CoV-2 infected animals. Remdesivir also reduces the pathological process, alleviates mild symptoms, and improves pulmonary lesions in SARS-CoV-2-infecetd animals. Remdesivir has been used as a compassionate drug for treating COVID-19 patients. Conclusion: Although remdesivir has shown potent antiviral activities, more efficacy assessments are urgently warranted in clinical trials.